Study of operative outcomes of proximal tibia fractures treated with locking plates - Parth Mcwan; Nisarg Shah (International Journal of Research in Orthopaedics, 2024)
Background: In this study we have studied the functional outcome of proximal tibial fractures treated by open reduction and internal fixation treated with locking compression plates after a minimum follow up period of 6 months. Methods: We conducted the study of 50 patients that aimed at assessing the functional outcomes of radiologically confirmed proximal tibia fracture (both intra articular and extra articular) treated using locking compression plates, between July 2020 to May 2022 at Department of Orthopaedics in our Institute. The Schatzker classification was used for classifying the fractures and planning the treatment strategy using plain radiographs and CT scan films. The treatment modality was decided after classifying the type of fracture, the displacement, and the amount of depression of the tibial plateau, in our study, we included only those patients who were undergone ORIF or MIPPO for definitive treatment. Results: Maximum number of patients (total 12) were in age group of 41-50 years (24%). Out of total 51 proximal tibia fractures, 4 (7.8%) were of type 1 variety, 12 (23.52%) were of type 2 variety, 2 (5.8%) were of type 3 variety, 4 (7.8%) were of type 4 variety, 6 (11.76%) were of type 5 variety and 9 (17.64%) were of type 6 variety according to Schatzker classification. out of 50 patients treated with locking compression plates, 26 patients (52%) showed excellent outcome with score between 28-30; 17 patients (34%) showed good outcome with score between 24-27; 7 patients (14%) showed fair results with score between 20-23, according to Modified Rasmussen’s scoring system. Conclusions: Locking compression plates (LCP) for the treatment of the proximal tibia fractures including difficult fracture situations seem to be good implant of choice for better post operative outcomes.